Doctoral supervisor’s views on building a Research Identity - Mokhampanyane, Matsolo Claurina; Segalo, Letlhoyo (Technium Social Sciences Journal, 2021)
Literature confirms that building a research identity forms the basis of good supervision. Also confirms that, it takes time and commitment, but every good supervisor needs to be a scholar in their field. The study’s main interest was quality value added to doctoral candidates as established researchers and how supervisors’ research identity transferred to doctoral students? In addition, the researcher wished to establish the supervisor’s responses to research identity and application thereof. A qualitative research study was used with a purposive sample of 10 doctoral supervisors at the time of research, were designated using knowledgeable sampling technique. Bourdieu’s homo academicus theory of cultural capital was used to frame academic identities of fit for purpose. Open-ended questionnaire was used to collect data from the participants. The data collected was analyzed using thematic analysis. This study reveals that active participation of supervisors in research is critical, as that is how good quality in research can be measured. The findings also revealed that role and responsibilities of doctoral supervisors could be derived from taking part in research and willingness to learn from others open for training, collaborations and supervision developments in order to develop their research identity in academia.